Increased panel height enhances cooling for photovoltaic solar farms. (1st November 2022) - Smith, Sarah E.; Viggiano, Bianca; Ali, Naseem; Silverman, Timothy J; Obligado, Martín; Calaf, Marc; Cal, Raúl Bayoán
Abstract: Solar photovoltaic (PV) systems suffer substantial efficiency loss due to environmental and internal heating. However, increasing the canopy height of these systems promotes surface heat transfer and boosts production. This work represents the first wind tunnel experiments to explore this concept in terms of array flow behavior and relative convective heat transfer, comparing model solar arrays of varied height arrangements - a nominal height, extended height, and a staggered height configuration. Analyses of surface thermocouple data show average Nusselt number ( N u ) to increase with array elevation, where panel convection at double height improved up to 1.88 times that of the nominal case. This behavior is an effect of sub-array entrainment of high velocity flow and panel interactions as evidenced through flow statistics and mean kinetic energy budgets on particle image velocimetry (PIV) data. The staggered height arrangement encourages faster sub-panel flow than in the nominal array. Despite sub-array blockage due to the lower panel interaction, heat shedding at panel surfaces promotes improvements on N u over 1.3 times that of the nominal height case. Highlights: Increasing the array height for solar photovoltaic farms also increases panel convection. Solar panel cooling is enhanced by increased flow beneath the array and mixing at the panel. Sub-panel solar array flow behaves similar to urban and vegetative canopies. Increased PV panel height enhances the sub-array momentum and kinetic energy entrainment accompanying relative cooling effects.